Dissolving Identities: The Representation of Alzheimer's in Marie Laberge's Oublier (1987), Robert Gravel's Il n'y a plus rien (1992) and Michel Tremblay's L'Impératif présent (2003). Issue 2 (July 2016) - Killick, Rachel
Abstract : Of all the degenerative diseases, Alzheimer's has a particular grip on the public interest and the collective imagination of the ageing populations of Western societies. In Québec the number of people affected currently stands at some 20, 000, with a quarter of a million sufferers predicted in twenty years' time. The failure of memory, the loss of social connection, the disappearance of self- and social awareness and the collapse of identity, all of them outrunning other bodily failures, are disturbing and harrowing features of the illness for sufferers themselves in the first instance, and increasingly, as degeneration runs its unstoppable course, for those around them. At the same time, the physiological particularities of the disease link into broader philosophical, psychological and social questions about the role of the memory in the constituting of individual and social identity, and about the conflicting pressures of autonomy and dependence in the field of personal and social interaction. These questions have always greatly interested creative writers, and the intensity of their refraction through the lens of Alzheimer's thus has a wide-ranging general relevance as well as being peculiarly topical. Representation of the illness on stage to a theatre audience poses however ethical and artistic challenges that substantially exceed the private, intimate modes of the novel and poetry. Some of the different ways in which playwrights in Québec have responded to these challenges, and their varying emphases on the complex impacts of the illness are examined here through a comparative and contrastive analysis of Marie Laberge's Oublier (1987), Robert Gravel's Il n'y a plus rien (1992) and Michel Tremblay's L'Impératif présent (2003).